A novel PPTA/PPy composite organic solvent nanofiltration (OSN) membrane prepared by chemical vapor deposition for organic dye wastewater treatment. (February 2022) - Lai, Xing; Wang, Chun; Wang, Liming; Xiao, Changfa
Abstract: In this study, a stable and controllable poly( p -phenylene terephthamide)/polypyrrole (PPTA/PPy) composite organic solvent nanofiltration (OSN) hollow fiber membrane was successfully prepared based on the robust chemical vapor deposition (CVD) method. The structure and properties of the prepared PPTA/PPy OSN membranes were studied in detail. Interestingly, after modifying by PPy, SEM showed that the surface of the membrane formed a layer of "Turing-like" structure and evenly covered the surface of the membrane. It was evident that the prepared PPTA/PPy OSN membranes achieved good dye-removal ability with a molecular weight cut-off range from 200 to1000 Da, and the rejection of negative dyes was higher than 93.4%. Especially at high temperature (80 °C) and organic solvent ( N, N -dimethylacetamide, DMAc), the PPTA/PPy OSN membranes still exhibited excellent permeation and separation performance. Furthermore, at room temperature, the immersion experiment of the fabricated PPTA/PPy OSN membranes in both ethanol and DMAc for one month also proved the stability of long-term organic solvents. Based on the above results, this work offered a novel PPTA based hollow fiber nanofiltration membrane, which was expected to be applied in thermal and organic dye wastewater treatment. Graphical abstract: Unlabelled Image Highlights: A controllable PPTA/PPy OSN membrane is produced by chemical vapor deposition. The PPTA/PPy OSN membrane shows greater separation performance at 80 °C and DMAc. Compared with traditional methods, chemical vapor deposition is easy to operate.